Open label multi-centre trial on efficacy and tolerability of microionized isotretinion therapy in treatment of moderate to severe acne vulgaris - Shah, Bela; Jangid, Neha; Naidu, Aswini A. (International Journal of Research in Dermatology, 2020)
Background: Isotretinion was approved by United States Food and Drug Administration (US FDA) in 1982 for the treatment of severe recalcitrant nodulocystic acne. Its conventional recommended dose has been 0.5-1.0 mg/kg body weight per day for 16-32 weeks, with a maximum cumulative dose of 120 mg/kg. Objective of the study was to assess the efficacy and tolerability of 24 week of once daily micronized isotretinoin therapy in the treatment of moderate to severe acne vulgaris was conducted. Methods: Total n=580 of patients were included with 249 (43%) male and 331 (57%) females. Patients were assessed at baseline 6, 12 and 24 weeks and 12 weeks post treatment follow-up based on the assessment of severity of acne vulgaris using global acne grading system (GAGS), assessment of improvement in lesion counts, global assessment of overall efficacy by doctor (based on overall assessment) and by patients (based on overall relief in symptoms) and overall assessment of drug tolerability. Results: In terms of improvement in lesions, excellent results from 4% (22) in week 6th has move to 34% (193) in week 24th. In terms of global efficacy examined by doctors, very effective results i.e. 40% (234) in 12th week has moved to 70% (403) in 24th week. In terms of drug tolerability, excellent results have moved from 119 patients to 190 patients by end of the study. Conclusions: Hence the micronized isotretinoin therapy had overall satisfactory outcome in the treatment of patients with moderate to severe acne vulgaris (grade 2, 3 and 4).